Software Based Approach for Classroom Teaching of Electrical Engineering Courses: A Case Study - Mehar, Hemant (Journal of Technical Education and Training, 2015)
Electrical engineering concepts are abstract in nature and difficult to explain using conventional teaching tools. The use of software in teaching holds the potential in providing better learning support as these tools can provide visual representations of complex circuits operation and waveforms for enhanced concept and procedural learning in power electronics. The software packages available for simulation of power electronic circuits include MATLAB, PSPICE and PSIM. In this study the author takes an example of an AC voltage controller to explain the software based teaching approach. The author used two software based simulation tools to explain the AC voltage controller concept and compare the software based approach with the blackboard and power point presentation based technique. Results of different approaches are compared in the last session of this paper, so it is helpful for the faculty of electrical engineering to find the various applications of MATLAB, SIMULINK and PSIM in teaching. Overall students find the simulation approach is helpful for their learning.